From my head to my toes - Raisman, Aly, 1994- (Henry Holt and Company, 2024)
"A joyful ode to loving and caring for our bodies, from Olympic gold medalist and advocate Aly Raisman and bestselling artist Bea Jackson. My body is my own. My body is just right for me, From my head to my toes. From My Head to My Toes gently introduces young readers to the topics of consent and bodily autonomy in a positive way. Cheerful and informative, this story focuses on the powerful message of self-love. Aly's inspiring words are paired with expert-vetted resources, giving adults the tools to begin having these essential conversations with kids from a young age."--Amazon.